2013
DOI: 10.1002/hep.26446
|View full text |Cite
|
Sign up to set email alerts
|

IL-25 prevents and cures fulminant hepatitis in mice through a myeloid-derived suppressor cell-dependent mechanism

Abstract: Fulminant hepatitis (FH) is a disease characterized by massive destruction of hepatocytes with severe impairment of liver function. The pathogenesis of FH is not fully understood, but hyperactivity of T cells and macrophages with excessive production of cytokines are important hallmarks of the condition. In this study, we investigated the role of interleukin (IL)225 in FH. IL-25 expression was evaluated in patients with FH and in livers of mice with FH induced by D-galactosamine (D-Gal) and lipopolysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…Among several pro-inflammatory cytokines involved, TNF-α and IFN-γ play a critical role in protecting mice from Con A-induced liver injury (Gantner et al, 1995;Kusters et al, 1996). Earlier reports demonstrated that cytokines TNF-α (Schumann et al, 2000) and IFN-γ (Sarra et al, 2013) were essential to trigger liver injury in Con A model, and we found that Con A stimulation triggers higher TNF-α and IFN-γ expression in serum. These variations of cytokine expression were in accordance with the observed changes in aminopherase activity and histopathology.…”
Section: Discussionsupporting
confidence: 62%
“…Among several pro-inflammatory cytokines involved, TNF-α and IFN-γ play a critical role in protecting mice from Con A-induced liver injury (Gantner et al, 1995;Kusters et al, 1996). Earlier reports demonstrated that cytokines TNF-α (Schumann et al, 2000) and IFN-γ (Sarra et al, 2013) were essential to trigger liver injury in Con A model, and we found that Con A stimulation triggers higher TNF-α and IFN-γ expression in serum. These variations of cytokine expression were in accordance with the observed changes in aminopherase activity and histopathology.…”
Section: Discussionsupporting
confidence: 62%
“…Hepatocytes are capable of producing IL-25 and decreased hepatic IL-25 expression has been reported in humans or mice with hepatitis (14). We established a HFD-induced model of hepatic steatosis in mice and evaluated a role of IL-25 in NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…The highest levels of IL-25 are found in the gastrointestinal tract and lung, where it is expressed primarily by epithelial cells and certain types of immune cells (8, 9, 1113). More recently, a study showed that hepatocytes were capable of producing IL-25 and decreased hepatic IL-25 was observed in animals or humans with hepatitis (14). Whether IL-25 is involved in regulation of lipid metabolism and associated hepatic steatosis is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies using dexamethasone show that its positive effect is specifically due to an increased MDSC induction [20]. Next to this, cannabidiol, a non-psychoactive cannabinoid and IL-25 treatment can reduce ConA induced inflammation and protect mice from liver injury by triggering the induction of MDSCs, opening a new window for therapeutic strategies [66,67].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Different therapeutic interventions have been shown to be associated with the induction and/or expansion of MDSCs during ConA-induced liver inflammation [20,66,67]. For example, treatment with glucocorticoids, which are strong anti-inflammatory molecules working through the GC receptor GR, led to accumulation of MDSCs and protected against liver injury [20,166].…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%